Business finance - Pitfield, Ronald R. (London : Gee & Co (Publishers) Limited, 1976)
The purpose of this book is to study the financial functions of commercial undertakings in relation to the sources of their finance. It therefore considers not only such accounting aspects as are relevant but also the economic, legal and procedural factors.
Including bibliographical references and index.
osa 21/01/2019
Loans
Keywords: Finance